Propuesta de solución al problema de inundaciones en la zona de las orquídeas de Guayaquil - Reyes Pincay, Brick (2016)
This article makes a hydraulic proposal to solve problems caused by flooding and improve urban resilience in Guayaquil, Ecuador. The city is seated on a flood plain -4 msnm- which has grown occupying potentially flood surfaces transforming them into living areas. The article analyzes the causes of floods in Las Orquìdeas area, a neighborhood located up north in the city. This floods are caused by the presence of heavy and sustained rains –Fenòmeno del Niño-, especially when they coincide with increasing levels of Daule river as a product of the flow of the tides whose hydropower enters the channels through the download sites of the urban hydrographic watershed of Las Orquideas. Those download sites are "Flor de Bastion, Inmaconsa, Bastion Popular, Las Orquídeas and Rio Daule. The article analyses the hydraulic behavior of the sites, the impact of flooding in the presence of large hydraulic infrastructure projects such as Daule Peripa dam and the low permeability of the soil. The hydraulic Proposal consists in freeing Las Orquídeas of the flow from the watershed through the implementation of a gate that diverts the flow to another channel before reaching the living area and download it into the Daule river